The Implementation of Handling Policy for Persons with Disabilities (A Case Study at Bina Grahita Social Care Institution in Nipotowe, Palu) - Wahyuni Nur Azizah; Lely Indah Mindarti; Firda Hidayati (Sekolah Pascasarjana Universitas Brawijaya, 2019)
The various problems faced by persons with disabilities or commonly referred to as disabled people are not only limited to the label as â€œthe poorâ€ but also their social welfare. Therefore, the problems of persons with disabilities also part of the nation and state development. The focus of this study is to identify, explore, and analyze the implementation of handling policy for persons with disabilities at Bina Grahita Social Care Institution (Panti Sosial Bina Grahita, abbreviated as PSBG) in Nipotowe, Palu through the policy implementation model developed by Edward III which includes several indicators such as communication, resources, disposition, and bureaucratic structure. This study is qualitative research in which the researchers examined the participantsâ€™ perspectives with interactive and flexible strategies. The location of the research was at Bina Grahita Social Care Institution of Nipotowe. The results showed that the Implementation of Handling Policy for Persons with Disabilities at Bina Grahita Social Care Institution of Nipotowe significantly influenced the policy-implementers and policy-recipients in accepting the policy. The resources owned by policy-implementers are inadequate staff, inadequate funding, and inadequate facilities and infrastructure. However, the information services are good and there is no misuse of authority. Besides that, in the context of implementing the handling policies for persons with disabilities, the disposition of various programs has been carried out well by the Government and the bureaucratic structure has been running properly such as SOP and fragmentation. The supporting factor for Handling Persons with Disabilities at Bina Grahita Social Care Institution of Nipotowe is the existence of clear regulations whereas the inhibiting factor is the improper system of staff promotion and transfers.